Long-term quality of life after decompressive craniectomy - Buffagni, Daniel; Zamarron, Alvaro; Melgosa, Isabel; Gutierrez-Gonzalez, Raquel (Frontiers in Neurology, 2023)
Introduction This study aims to assess the quality of life (QoL) in patients who have undergone decompressive craniectomy (DC) for any pathology that has caused life-threatening intracranial hypertension. Similarly, it aims to evaluate QoL perceived by caregivers or external informants. In addition to that, the last purpose is to determine which clinical or therapeutic factors could correlate with a better QoL. Methods A single-center cross-sectional study was designed. All patients over 18 years old who underwent a supratentorial DC at our department due to intracranial hypertension of any etiology, from January 2015 to December 2021, were retrospectively selected. Patients with incomplete follow-up (under 1 year from the event or those who died) or who declined to participate in the study were excluded. QoL was assessed with SF-36 and CAVIDACE scales. The correlation between clinical and therapeutic variables and SF-36 subscales was studied with Spearman's correlation and the Mann–Whitney U-test. Results A total of 55 consecutive patients were recruited: 22 patients had died, three were missed for follow-up, and 15 declined to participate, thus 15 subjects were finally included. The mean follow-up was 47 months (IQR 21.5–67.5). A significant reduction in the “role physical” and “role emotional” subscales of SF-36 was observed compared with the general population. According to caregivers, a significant reduction was assigned to the “physical wellbeing” and “rights” domains. The “physical functioning” score was poorer in women, older patients, those with dominant hemisphere disease, those who required tracheostomy, and those with poor outcomes in the modified Rankin scale. A strong correlation was found between the QoL index at the CAVIDACE scale and the SF-36 subscales “physical functioning” and “role physical”. Conclusion Most patients and caregivers reported acceptable QoL after DC due to a life-threatening disease. A significant reduction in SF- 36 subscales scores “role limitation due to physical problems” and “role limitation due to emotional problems” was referred by patients. According to caregivers' QoL perception, only 25% of the survey's participants showed low scores in the QoL index of the CAVIDACE scale. Only 26.7% of the patients showed mood disorders.